2020
DOI: 10.1029/2020gl088894
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by ENSO of the Relationship Between Stratospheric Sudden Warming and the Madden‐Julian Oscillation

Abstract: The ENSO modulation on the relationship between the Madden‐Julian Oscillation (MJO) and major stratospheric sudden warming (SSW) in the Northern Hemisphere winter is analyzed. The results indicate that the statistical relationship between the MJO and SSWs is robust during La Niña years but almost nonexistent during El Niño years. During La Niña years, a significant response of stratospheric temperature appears after certain MJO phases with a distribution consistent with MJO periodicity, whereas the response be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In contrast, two of these three occurred during La Nina and the third during neutral ENSO, which tends to lead to a stronger monthly mean vortex and a reduced probability of easterly winds in the full hindcast ensemble for the models considered by Garfinkel et al (2019). However, over the period considered in this study the observed relationship between ENSO and SSW was opposite, with more SSWs during La Nina (Domeisen et al, 2019), and ENSO also may modulate the impact of the MJO on SSWs (Ma et al, 2020). Favorable precursors -in particular El Nino, MJO Phase 5, and eQBO-were present before the well-predicted 1 January 2019 event as well .…”
Section: Resultsmentioning
confidence: 64%
“…In contrast, two of these three occurred during La Nina and the third during neutral ENSO, which tends to lead to a stronger monthly mean vortex and a reduced probability of easterly winds in the full hindcast ensemble for the models considered by Garfinkel et al (2019). However, over the period considered in this study the observed relationship between ENSO and SSW was opposite, with more SSWs during La Nina (Domeisen et al, 2019), and ENSO also may modulate the impact of the MJO on SSWs (Ma et al, 2020). Favorable precursors -in particular El Nino, MJO Phase 5, and eQBO-were present before the well-predicted 1 January 2019 event as well .…”
Section: Resultsmentioning
confidence: 64%
“…However, over the period considered in this study the observed relationship between ENSO and SSW was opposite, with more SSWs during La Nina (D. I. Domeisen et al, 2019), and ENSO also may modulate the impact of the MJO on SSWs (Ma et al, 2020).…”
Section: Resultsmentioning
confidence: 69%
“…Since the discovery of SSW [3], it has attracted wide attention, including its classification [1,4], mechanism [5], and its prediction by models [6,7]. A series of studies have demonstrated that several factors can influence SSW events, such as Quasi-Biennial Oscillation (QBO), El Nino-Southern Oscillation (ENSO), and Madden-Julian Oscillation (MJO) [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Garfinkel et al [16] further indicated that MJO phase 7 (defined by Wheeler and Hendon [17]) leads to a North Pacific low and then a weakened polar vortex, which favors the onset of SSW, while MJO phase 3 plays an opposite role. Ma et al [12] showed that the MJO-SSW relationship can be modulated by ENSO. In addition, Wang et al [18] discussed the link between the frequency of MJO phases and the interannual variability of stratospheric wave activity (SSW is a phenomenon of the extremely strong stratospheric wave activity) in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%